Theoretical and practical aspects of infiltration gallery planning and design. - Castro, Peter M. (UPCOE NEC Technical Bulletin)
The range of yields that may be expected through wet and dry periods is initially estimated for the candidate site. Alternative layouts of gallery pipes are configured in accordance with this range of yields. A groundwater flow model is employed to obtain the expected production rate for each alternative. Promising configurations are selected for design of pipe layouts, sizes, and pumping schemes. Site investigations should be comprehensive so as to avoid wasting time and resources on sites that would likely turn out infeasible. Gallery pipes in high yield sites should be designed to flow full, while in low yield sites the pipes would have free surface flow.